Techno-economic analysis for a stand-alone hybrid power system: A case study, in Istanbul, Turkey - (:unkn) unknown (SILA SCIENCE, 2012)
This study presents a techno-economic evaluation of a stand-alone hybrid power system. The system consists of three energy sources, photovoltaic (PV) panels, a wind turbine and a proton exchange membrane fuel cell (PEMFC). PV and wind turbine is the main sources for the system and the fuel cell performs as a backup power source. Therefore, continuous energy supply needs energy storing devices.
Keywords: Stand-alone hybrid power system; Unit sizing; Economical analysis; ENVIRONMENTAL-ANALYSIS; ENERGY; GENERATION; DENSITY; COST; DESIGN; PLANTS